2018
DOI: 10.1080/10942912.2018.1479861
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the antibacterial activity and the main bacteriostatic components from bayberry fruit extract

Abstract: This study evaluated the inhibitory effects of samples extracted by different solvents from bayberry on eight common foodborne pathogens and investigated the main bacteriostatic components of bayberry extracts using ultraviolet and ultraperformance liquid chromatographic-electrospray mass spectrometry. Among the different solvent extracts, the waterextracted sample (BE1) had the greatest average inhibition zone diameter for the tested foodborne pathogens, which reached 22.1 mm. Among them, Salmonella paratyphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…MIC values were 0.625-0.5 mg/mL, and MBC values were 2.5 or 5 mg/mL. The crude extract of fungus YG-2 had the highest TPC and the best antibacterial effect, which was consistent with the results of Ju et al (2018) , whose experimental results showed that water extraction of bayberry extract had the highest TPC and antibacterial activity among four solvents. That is, the minimum MIC and MBC of the YG-2 crude extract may be due to its highest TPC.…”
Section: Discussionsupporting
confidence: 81%
“…MIC values were 0.625-0.5 mg/mL, and MBC values were 2.5 or 5 mg/mL. The crude extract of fungus YG-2 had the highest TPC and the best antibacterial effect, which was consistent with the results of Ju et al (2018) , whose experimental results showed that water extraction of bayberry extract had the highest TPC and antibacterial activity among four solvents. That is, the minimum MIC and MBC of the YG-2 crude extract may be due to its highest TPC.…”
Section: Discussionsupporting
confidence: 81%
“…Consumer demand for natural antibacterial and antiseptic substances has grown as abuse of toxic synthetic food preservatives and antibiotics has become more widespread (Ju et al, 2017). Recent findings from our laboratory revealed the BE had a significant bacteriostatic effect (Ju et al, 2018). In addition, in previous studies, we also found that BE has a good effect on the treatment of diarrhea (Yao et al, 2011).…”
Section: Introductionmentioning
confidence: 54%
“…is an edible fruit native to East Asia with popularity for its attractive color and delicious taste, and is also highly valued for its nutritional and medicinal properties ( Ren et al, 2021 , Sun et al, 2013 , Zhang et al, 2022a ). Modern pharmacological studies have proved that bayberry extracts possess multiple biological activities, including antioxidant, anti-inflammatory, anti-diabetic, and anti-cancer effects owing to the presence of various bioactive compounds like vitamins, flavonoids and phenolic acids ( Ju et al, 2018 , Liu et al, 2020 , Lyu et al, 2021 , Tu et al, 2022 , Zhang et al, 2022a ). Due to the extreme perishability of the fresh fruit, the harvested bayberries are often used for processing, in addition to fresh consumption.…”
Section: Introductionmentioning
confidence: 99%